Formulating Cryptocurrencies Dynamic Portfolio with Consumption Sectors’ Stocks - Naufal Dwinanda Narra Putra; Robiyanto Robiyanto; Hans Hananto Andreas (Media Ekonomi dan Manajemen, 2022)
This study was conducted to analyze the performance of the portfolio formed with different asset classes. The instrument used is the consumption sector index with 5 cryptocurrencies. Does the formed portfolio have a better performance than the portfolio that is only formed from the consumption sector index. The type of data in this study uses secondary data in the form of a daily frequency time series with a research period from January 2019 to January 2021. The data in this study used quantitative data. Portfolio performance measurement in this study was measured using the ratio of Sharpe, Treynor, Jensen, Sortino, and Omega. Based on the results of the study, it shows that the performance of the consumption sector index portfolio that is hedged with cryptocurrency produces a higher rate of return in the period during the pandemic than in the period before the pandemic. However, there is 1 crypto that produces negative values in each ratio and research period, namely Tether. Overall, the results of this study can be concluded that adding cryptocurrency to the formation of a portfolio will get a better portfolio performance.